Meningkatkan Keterampilan Profesional Mahasiswa: Strategi Penguatan Soft Skills untuk Sukses di Era Digital - Huda, Nurul; Istiawan, Deden; Masitha, Alya; Mahiruna, Adiyah (Fakultas Teknik Universitas Cenderawasih, 2024)
This community service program aims to equip students with knowledge and skills relevant to facing the challenges of the digital workforce. The activity was attended by 40 students, with materials covering four main topics: Understanding the Digital Era Workforce, Key Soft Skills for the Digital Era, Building Competencies for the Digital Workforce, and Preparing for Career Success. In addition, participants were guided in creating an individual Action Plan to prepare themselves for career success in the future. The methods used in this program included material presentations, interactive discussions, and the development of personal action plans, aiming to enhance both technical and non-technical skills needed in the digital workforce. Evaluation results show that 75% of students rated the material as excellent, 20% as good, and 5% found it somewhat beneficial. This indicates the program’s success in providing significant value to participants. This program is expected to enhance students' readiness to enter the increasingly digital and technology-driven job market, while providing valuable insights for planning and developing their careers. Moving forward, this activity can serve as a model for developing more effective community service programs that align with the needs of the modern workforce.